2013
DOI: 10.1089/dna.2012.1776
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of BRAF V600E Mutation in Papillary Thyroid Carcinoma and Tumor-Surrounding Nontumoral Tissues

Abstract: The aim of this study was to investigate the association between the BRAF V600E mutation incidence and histopathologic prognostic risk factors for papillary thyroid carcinoma (PTC) on the Turkish population. The contribution of BRAF V600E mutation in both tumor and tumor-surrounding nontumoral tissues of 108 patients with PTC was assessed using mutant allele-specific amplification-polymerase chain reaction. The BRAF V600E mutation was found in 52.8% of the tumor tissues, and 7.4% of the tumor-surrounding nontu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…One possible mechanism of two identical somatic mutations arising in two different tumors is that BRAF mutations can be found in tumor-surrounding nontumoral tissues. This has specifically been described in PTC [ 13 ] as well as melanomas where BRAF mutations were present in normal skin distant from nevi [ 14 ]. It should be noted that both LCH and PTC were present within the thyroid in our case.…”
Section: Discussionmentioning
confidence: 96%
“…One possible mechanism of two identical somatic mutations arising in two different tumors is that BRAF mutations can be found in tumor-surrounding nontumoral tissues. This has specifically been described in PTC [ 13 ] as well as melanomas where BRAF mutations were present in normal skin distant from nevi [ 14 ]. It should be noted that both LCH and PTC were present within the thyroid in our case.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have evaluated the association between the BRAF (V600E) mutation, clinicopathological features and clinical outcomes of PTC; however, controversial results have been obtained for a correlation between the BRAF (V600E) mutation and clinicopathological features (1,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Furthermore, multiple previous studies have demonstrated a correlation between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC, including older age at diagnosis, male gender, large tumor size, the presence of extrathyroidal extension, lymph node and distant metastasis and an advanced stage (9)(10)(11)13,15,16,(18)(19)(20)28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated potential associations among the BRAF (V600E) mutation, clinicopathological features of PTC and the clinical outcome of patients; however, correlations between the incidence of the BRAF (V600E) mutation and clinicopathological features in PTC patients remains controversial (1,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Beside this, thyroid carcinoma was the third most common malignancy in both gender (12%) in Turkey and the second most common malignancy among Turkish women (12%) according to the 2017 Turkish health ministry official cancer report (http://kanser.gov.tr) . In Turkey, the incidence of thyroid carcinoma has increased from 10.8 per 100,000 individuals in 2006 to 20.7 per 100,000 individual in 2014, representing approximately a 2-fold increase (Daglar-Aday et al, 2013).…”
Section: Introductionmentioning
confidence: 99%